Techno-Economic Analysis of CO2 Capture Reference System Based on Phase-Change Solvent Absorption - Wei, Dixin; Peng, Chang (My University, 2017)
The CO2 emission into atmosphere over the past century is considered as the main reason for global warming phenomenon. The Paris Agreement target of 2 C urged not only focus on this issue, but also effective measures for the transition period and long term. The solvent based post-combustion carbon capture, a conveniently applied process,can be costly mainly due to high reboiler heating for the solvent regeneration. If the cost can be reduced to an acceptable value for power plants, then PCC processes exhibit substantial potential in coal and natural gas fired plant emission reduction, which is a large share in global CO2 emissions. This study focuses on phase-change amines, that have reported good experimental results in phase separation, and thus reduce reboiler heating demand. It starts with checking and comparing a group of amines and selecting potential candidates. Further PCC process simulation in Aspen shows detailed results in performance of different configuration and amine type. In general, two amines known as DIBA and HXA are seen as promising replacement, especially HXA. The results are compared with MEA reference case. With respect to reboiler duty, the two selected amines both showed more than 50% reduction. And in the best scenario, the reboiler heating demand is reduced to 0.91 GJ/ton CO2 captured.
Keywords: Energiteknik; Energy Engineering